Biocides Effect on the Microbiologically Influenced Corrosion of Pure Copper by Desulfovibrio sp. - Onan, Mert; Ilhan-Sungur, Esra; Gungor, Nihal Dogruoz; Cansever, Nurhan (KOREAN ELECTROCHEMISTRY SOC, 2018)
The aims of this study were to determine the corrosion behavior of pure copper in the presence of Desulfovibrio sp. and also to investigate the effects of glutaraldehyde (GD) and isothiazolinone (ISO) on the corrosion behavior of pure copper in the presence of this sulfate-reducing bacteria (SRB) strain by using electrochemical techniques. Electrochemical measurements of pure copper were carried out at specified time intervals (0, 8, 24, 48, and 96 hr) over a period of exposure. Corrosion rates of pure copper from anodic and cathodic Tafel slopes and corrosion potential (E-corr) were determined. Biofilm and corrosion products on the copper surfaces were observed by Field Emission Scanning Electron Microscopy (FESEM) and Energy Dispersive X-Ray Spectrometry (EDS) analyses. The effects of solution types (PC (Postgate's C medium) and SRB (Desulfovibrio sp.)) and exposure times of copper and biocides (ISO or GD) on the corrosion rates of pure copper were evaluated by statistical analyses. As a result of the FESEM analysis, biofilm formation was observed on the surfaces of pure copper exposed to the Desulfovibrio sp. cultures both with and without the biocides. The results show that the pure copper was corroded by Desulfovibrio sp. However, the addition of GD or ISO to the Desulfovibrio sp. culture resulted in a decrease in the corrosion rate of the pure copper. It was also observed that both of the biocides showed a similar effect on pure copper's corrosion rate caused by Desulfovibrio sp.
Keywords: Pure copper; Microbiologically influenced corrosion (MIC); Desulfovibrio sp.; Biocide; Glutaraldehyde Isothiazolinone; SULFATE-REDUCING BACTERIA; MILD-STEEL; TAP WATER; BEHAVIOR; BIOFILMS; BRASS; Electrochemistry